2012
DOI: 10.1152/japplphysiol.00782.2012
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in Achilles tendon properties and triceps surae muscle architecture in vivo

Abstract: This study examined the concurrent age-related differences in muscle and tendon structure and properties. Achilles tendon morphology and mechanical properties and triceps surae muscle architecture were measured from 100 subjects [33 young (24 ± 2 yr) and 67 old (75 ± 3 yr)]. Motion analysis-assisted ultrasonography was used to determine tendon stiffness, Young's modulus, and hysteresis during isometric ramp contractions. Ultrasonography was used to measure muscle architectural features and size and tendon cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
218
9
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(257 citation statements)
references
References 52 publications
28
218
9
2
Order By: Relevance
“…The width of the Achilles tendon on the left side, and the length on both the right and left sides were significantly smaller in the age group 18-29 when compared to other age groups (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), and 50-50+). Stenroth et al [39] showed that tendon cross-sectional area was 16% larger in the older groups.…”
Section: Width Thickness Area Lengthmentioning
confidence: 94%
“…The width of the Achilles tendon on the left side, and the length on both the right and left sides were significantly smaller in the age group 18-29 when compared to other age groups (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), and 50-50+). Stenroth et al [39] showed that tendon cross-sectional area was 16% larger in the older groups.…”
Section: Width Thickness Area Lengthmentioning
confidence: 94%
“…Many studies have assumed that several additional characteristics and the biomechanical properties of the musculoarticular complex could influence muscle fascicle behavior (6,20,41,54). Therefore, they can also affect the efficiency of muscle fiber dynamics by allowing a reduction of fascicleshortening velocity to produce very high angular velocity, especially during human locomotion (running, jumping) (39).…”
Section: Relationship Between Angular Velocity Reached In Nlc and Biomentioning
confidence: 99%
“…Stiffness of both animal and human tendons have been reported to increase (Shadwick 1990;Kubo et al 2007a), decrease (Stenroth et al 2012), or remain unchanged (Couppe et al 2009) with aging. Vidiik et al (Viidik et al 1996) showed that life-long endurance training may have counteracting systemic effects on the aging process as reflected by less stiff tail tendon tissue.…”
Section: Tendon Mechanical Propertiesmentioning
confidence: 99%
“…In line with this, we recently demonstrated that both enzymatic hydroxylysyl pyridinoline (HP) and lysyl pyridinoline (LP) cross-links and pentosidine, which is a marker of AGE, were more abundant in the patellar tendon of old men compared with that of young men (Couppe et al 2009). It is believed that greater AGE cross-link density increases tendon stiffness (Reddy et al 2002;Galeski et al 1977;Andreassen et al 1988;Bai et al 1992), however, mechanical properties of both animal and human tendon has been reported both to increase (Nielsen et al 1998;Shadwick 1990;Kubo et al 2007a;Wood et al 2011), decrease (Stenroth et al 2012; Karamanidis and Arampatzis 2006;Dressler et al 2002;Onambele et al 2006;Mian et al 2007) or remain unaltered with aging (Couppe et al 2009;Haut et al 1992;Hubbard and SoutasLittle 1984;Johnson et al 1994;Carroll et al 2008). Thus, to what extent aging influence mechanical properties of tendon tissue remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%